Li3V2(PO4)3 cathode materials for lithium-ion batteries : a review - Rui, Xianhong (2014)
The principal challenges facing the development of lithium ion batteries (LIBs) for hybrid electric/plug-in-hybrid (HEV/PHEV) vehicles and for off-peak energy storage are cost, safety, cell energy density (voltage × capacity), rate of charge/discharge, and service life. There are exciting developments in new positive electrode (cathode) materials to replace the LiCoO2 for use in the LIBs over the past decade. Monoclinic Li3V2(PO4)3 (LVP) with promising electrochemical properties including excellent cycling stability, high theoretical capacity (197 mAh g-1), low synthetic cost, improved safety characteristic, and low environmental impact emerges as highly suitable candidate. In this review, we focus on research work related to the LVP and discuss its host structure, mechanism of lithium insertion/extraction, transport properties (i.e., electronic conductivity, and lithium diffusion), synthesis and electrochemical properties. We highlight some recent development of LVP, which shows superior cycling stability and high rate capability and give some vision for the future research of LVP based electrode.